Perbandingan Efektivitas Terapi Ekstrak Ikan Gabus Dengan Putih Telur Dan Human Albumin 20% Terhadap Peningkatan Kadar Albumin Pasien Hipoalbuminemia Di RSUD dr. Zainoel Abidin - Ferry Erdani; Rita Novika; Ika Fitri Ramadhana (LITBANG RSUDZA, 2021)
Hypoalbuminemia is a condition where blood albumin levels are less than 3.5 g/dL. In this condition, there will be disruption to the physiological processes in the body. There is a relationship between low albumin levels with an increased risk of infectious complications, a high mortality rate in hospitalized patients, both non-surgical and surgical patients. To restore the important function of albumin, intervention is needed to increase albumin levels in the blood. Human albumin infusion is the most common. However, because of the high price, many other alternatives have been investigated to increase plasma albumin levels. This study aims to determine the effectiveness of snakehead fish extract therapy, compared with egg white and 20% human albumin in increasing albumin levels in hypoalbuminemic patients so that it can save costs and can improve the quality of life of hypoalbuminemia. This research is a quantitative research with Randomized Control Trial design. Samples were collected from August to October 2021 in the surgical inpatient ward of RSUD dr Zainoel Abidin. Data were collected from 36 samples, then divided into 3 treatment groups, namely the egg white group, the snakehead fish extract group and the Human Albumin group. The study used a randomized, blinded clinical trial. The data taken is albumin levels. The data were tested for normality with the Kolmogrov-Sminrnov test, then continued with the ANOVA test. The results obtained 36 samples that meet the inclusion criteria. The average level of increase in the egg white group was -0.0792 (Sig. 0.51), the snakehead fish extract group was 0.1625 (sig. 0.429) and the Human Albumin group was 0.237 (sig. 0.431). From the results of these studies giving snakehead fish extract can be an alternative therapy to treat hypoalbuminemia conditions.Keywords: Hypoalbuminemia, Albumin, Egg white, Snakehead Fish Extract, Human Albumin